2020
DOI: 10.1155/2020/7460781
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Botany, Traditional Use, Phytochemistry, Analytical Methods, Pharmacological Effects, and Toxicity of Angelicae Pubescentis Radix

Abstract: Angelicae Pubescentis Radix (AP), as a traditional Chinese medicine (TCM), has been used for thousands of years in China. In this paper, the botany, traditional use, phytochemistry, analytical methods, quality control, pharmacological effects, and toxicity of AP were reviewed. It can provide a reference for the further research and lay a foundation for the rational clinical application of AP. The relevant information on AP was collected from scientific databases (such as Baidu Scholar, CNKI, Google Scholar, Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Clinical statistical studies have shown that DXHP is one of the most frequently used Chinese medicine pairs in the treatment of OA [23]. In modern pharmacological research, the active ingredients in DH are linked to antioxidant, antiinfammatory, and analgesic efects [24], while the active components of XD purportedly protect against bone loss, promote cartilage formation, and improve bone metabolism [25]. In addition, the pharmacological compatibility mechanism of DXHP is similarly refected in the TCM theory.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical statistical studies have shown that DXHP is one of the most frequently used Chinese medicine pairs in the treatment of OA [23]. In modern pharmacological research, the active ingredients in DH are linked to antioxidant, antiinfammatory, and analgesic efects [24], while the active components of XD purportedly protect against bone loss, promote cartilage formation, and improve bone metabolism [25]. In addition, the pharmacological compatibility mechanism of DXHP is similarly refected in the TCM theory.…”
Section: Introductionmentioning
confidence: 99%
“…f. biserrata Shan et Yuan. It has the functions of removing wind and dehumidification and relieving paralytic pain [ 13 ]. Clinically, it has a good clinical effect on arthritis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies have shown that phenolic acid compounds also have a certain anti-inflammatory effect [ 19 ]. However, the current research study on the antiarthritic effect of APR is limited to the level of pharmacodynamics and pharmacodynamic material basis, and there are few pharmacokinetic studies of its active components, and most of the pharmacokinetic studies of APR have been conducted in normal experimental animals [ 13 , 15 , 20 , 21 ]. For example, Qian et al used HPLC-DAD to determine columbianetin in normal rat plasma [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations